O processo do reconhecimento em Henri Bergson: metafísica do tempo e da memória - Lied, Úrsula Maria Coelho (2019)
The purpose of this work is to demonstrate as the Metaphysics of Bergson about time and memory have lead him to their thesis about acknowledgement. The entanglement between these subjects was apresentate in Matter and Memory, but is in a later course, about the History of Theories of Memory, that Bergson has work both topics with relation a specific problem, the acknowledgement. How we akcknowledgement a object, a person or a sound, for example? The investigation of as happen the proccess of acknowledgement give from the bergsonian conception of time and memory because, for Bergson, the acknowledgemente is a union between past and present and between perception and memory. However, the perception that participate of to acknowledgement's act isn't a commum perception, it's that Bergson call dynamic scheme. Thus, the acknowledgement depends of a proccess in which are envolved the informations evocade by the memory (souvenirs) and the data grant from the perception in the present moment. Bergson claim that there are three types of acknowledgement, two are impersonal and one is personal. In the motor acknowledgement, although no are evocation of memories, there are unconscious participation of the movements that were learn in the past. The acknowledgement of images correspond to the situations in which we identificate the more several objects, places, words. The third type of acknowledgement is called for Bergson of personal acknowledgement because the subject acknowledgement the presented informations as like making part of your own history. Namely, while the two first types of acknowledgement don't envolve the own history of subject, the third type require necessarly that the subject evoque the past relation between him and the perceived object. During the elaboration of your ideas about the acknowledgement, Bergson examine some memory's theories, some previous to him other contemporaneous to him. Among these theories, Bergson grant mainly attention to the called associacionist psychology because consider it flawed in several points. All the bergsonian argumentation about the proccess of the acknowledgement depends on your theory of memory, that is, in turn, linked to the bergsonian notion of time. Thus, the Bergson's thesis about acknowledgement result of yours metaphysical hypothesis about time and memory. Your investigation on nature of past, present, memory and perception and about the relations among them lead him to the conclusion that the acknowledgement's act is a moment of cooperation among all these elements.